"We are building a nation": CAMFED's Learner Guide program is transforming prospects for young people. Issue 1 (2nd January 2021) - Martin, Diris; Mponji, Doris
Abstract : Mentorship from within the community holds great promise for transforming the lives of young people and helping them to take full advantage of educational opportunities.